The influence of iconicity and autistic traits on novel word learning: a cross-cultural investigation - Vijayachandra Ramachandra; Kairi Sugimoto; Kelly Ziskind; Ark Verma; Irfan Ahmad; Mahayana Godoy; Katsumi Watanabe (Royal Society Open Science)
The effects of iconicity and autistic traits on novel word learning were investigated through an online experiment involving 1481 healthy adult participants aged between 18 and 40 years from four countries: Brazil (N = 261), India (N = 416), Japan (N = 493) and the USA (N = 311). Participants completed a bouba–kiki-based word learning task, viewing novel images paired with either iconic names (congruent condition) or arbitrary names (incongruent condition). Word recognition was assessed using a three-alternative forced-choice procedure, and autistic traits were measured with the autism spectrum quotient (AQ). Results showed a significant benefit of iconicity across all countries, with better performance in the congruent condition. While a linear mixed model revealed no significant effect of AQ on bouba–kiki scores overall, a country-specific analysis found a weak but significant positive correlation between AQ scores and bouba–kiki performance in Japanese participants. This country-specific finding should be interpreted cautiously and warrants further exploration. Overall, the findings demonstrate the robustness and universality of the bouba–kiki effect on word learning across both Western and Eastern cultures. However, the relationship between autistic traits and iconicity was not consistent across all countries and may depend on cultural factors. Further research is needed to explore this in more detail.